Imunoterapie v prevenci a léčbě karcinomu prsu - Svoboda, M; Navrátil, J; Slabý, O (Klinicka onkologie, 2015)
The immune system is believed to play a dual role in carcinogenesis. On one hand, it could prompt tumorigenesis and cancer progression, on the other hand, it has the capacity to eradicate tumor cells. There has been an evidence of natural immunogenicity in breast cancer and we have also witnessed several attempts to stimulate non-specific antitumor immune response (Coleys toxin, BCG vaccine etc.). New technologies and further knowledge of molecular basis of immune system and its function encouraged the development of effective immunotherapy capable of inducing a solid antitumor activity. These agents appear promissing in the prevention and therapy of breast carcinoma as well. The assumption is based on the results of several antitumor vaccine trials targeted against HER2, MUC1, CEA and mammaglobin-A, as well as immune checkpoint inhibitors (e.g. CTLA-4, PD-1/ PD-L1, LAG3). With regards to different mech-anisms of action of these agents, their combination might bring about synergistic antitumor effects. Nonetheless, monoclonal antibodies and cytostatic agents already approved for breast cancer treatment might be exploited for their immunomodulation effect as well. This article addresses prospects for immunotherapy of breast carcinoma in detail.
Keywords: Female; nádory prsu; lidé; Breast Neoplasms; Immunotherapy; ženské pohlaví; Humans; imunoterapie